Gender Differences in Mortality After Left Ventricular Assist Device Implant: A Causal Mediation Analysis Approach. Issue 6 (13th October 2020) - Nayak, Aditi; Hu, Yingtian; Ko, Yi-An; Mehta, Anurag; Liu, Chang; Pennington, John; Xie, Rongbing; Cowger, Jennifer; Kirklin, James K.; Kormos, Robert L.; Simon, Marc A.; Morris, Alanna A.
Abstract : Supplemental Digital Content is available in the text. Abstract : We used the International Society for Heart and Lung Transplantation (ISHLT) Registry for Mechanically Assisted Circulatory Support (IMACS) database to examine 1) gender differences in post-left ventricular assist device (LVAD) mortality in the contemporary era and 2) preimplant clinical factors that might mediate any observed differences. Adults who received continuous-flow (CF)-LVAD from January 2013 to September 2017 (n = 9, 565, age: 56.2 ± 13.2 years, 21.6% female, 31.1% centrifugal pumps) were analyzed. An inverse probability weighted Cox proportional hazards model was used to estimate association of female gender with all-cause mortality, adjusting for known covariates. Causal mediation analysis was performed to test plausible preimplant mediators mechanistically underlying any association between female gender and mortality. Females had higher mortality after LVAD (adjusted hazard ratio [HR]: 1.36; p < 0.0001), with significant gender × time interaction ( p = 0.02). An early period of increased risk was identified, with females experiencing a higher risk of mortality during the first 4 months after implant (adjusted HR: 1.74; p < 0.0001), but not after (adjusted HR: 1.18; p = 0.16). More severe tricuspid regurgitation and smaller left ventricular end-diastolic diameter at baseline mediated ≈21.9% of the increased early hazard of death in females; however, most of the underlying mechanisms remain unexplained. Therefore, females have increased mortality only in the first 4 months after LVAD implantation, partially driven by worsening right ventricular dysfunction and LV-LVAD size mismatch.